PERANCANGAN SISTEM INFORMASI AKADEMIK SEKOLAH BERBASIS WEBSITE DENGAN LARAVEL 5 PADA SMK NEGERI 1 CILELES - Irma Yunita Ruhiawati; Siti Sopiah (Jurnal Ilmiah Sains dan Teknologi, 2019)
Technological developments that occur today are very influential on all aspects ranging from sales, trade also in the aspect of education. Aspects of education is a slightly behind aspects of the technology world. SMK Negeri 1 Cileles is one of the State schools in the area of ​​South Banten. It has two departments namely Office Administration and Computer and Network Engineering. With the condition of the region is very left behind both from infrastructure, tbsp and also from the field of technology. Because the condition is very difficult for teachers, students and staff TU in carrying out its duties. From the results of direct observations made, the authors found the problems that occur such as the absence of a computerized absence system, the unavailability of online administration facilities for both teachers, students and staff TU, ​​not available ebook for students to support technology-based learning in accordance with the Curriculum 2013. The purpose of this Thesis Proposal is the author is expected to help SMK Negeri 1 Cileles to create academic information systems for computerized penyabsenan system, thus citizens in SMK Negeri 1 can work quickly and accurately in making attendance reporting. This research method using waterfall method. For that from the description above, the authors are interested to take the title of Thesis Proposal: "Design of Academic Information Systems School Based Website with Laravel 5 At SMK Negeri 1 Cileles".